El control y acceso al patrimonio bibliográfico a través de los catálogos disponibles en Internet - Orera Orera, Luisa (Documentación de las Ciencias de la Información, 2007)
This study explains the concept of bibliographic heritage, analyses the role played by libraries in the preservation and access to it, and presents catalogues as fundamental tools to carry out both functions. The paper classifies the catalogues according to their characteriological affinity and offers a number of significant examples of catalogues that include historical heritage, such as the Spanish Bibliographic Heritage Union Catalogue and others belonging to the Association of Latin American States for the Development of National Libraries in Latin American Countries (ABINIA).